A dual-band THz absorber based on graphene sheet and ribbons. (1st March 2018) - Xing, Rui; Jian, Shuisheng
Highlights: The proposed absorber can realize dual-band absorption at 4.95 THz in 99.8% and at 9.2 THz in 99.6%. The absorption peaks can be tuned by adjusting the chemical potential of graphene. The structure of the absorber is very simple and it can be manufactured by chemical vapor deposition (CVD). It shows a great prospect in optical detection and sensing, thermal applications and sub-wavelength optical devices. Abstract: A dual-band graphene absorber is proposed and investigated in this paper. The absorber consists of the gold substrate, the graphene sheet sandwiched by dielectric layers and the array of graphene ribbon placed on the top. The two absorption peaks of the dual-band are 99.8% at 4.95 THz and 99.6% at 9.2 THz, respectively. Due to the characteristic of tunable surface conductivity of graphene, the absorption can be controlled by adjusting the chemical potential of graphene. We also investigate the dependence of the absorption curve of the proposed absorber on the structure parameters. In addition, the structure of the absorber is very simple and it can be manufactured by chemical vapor deposition (CVD).